Standard of Micro-Credential Quality Management System To Enhance Employability and Competitiveness of Graduates - Surono, Surono (Pelopor Publikasi Akademika, 2024)
The development of a Micro-Credential Quality Management System (QMS) aims to ensure that micro-credentials are of high quality and aligned with industry needs. Micro-credentials provide formal recognition of specific competencies acquired through short-term, focused learning, offering an efficient means to address the rapidly evolving labor market and technological landscape. This research adopts a Research and Development (R&D) methodology, involving a preliminary study, system development, pilot testing, and validation, to create a robust QMS framework. The QMS focuses on establishing clear standards, rigorous assessment processes, continuous improvement, and collaboration with industry stakeholders to validate competencies. The pilot testing of the QMS in vocational high schools demonstrated its effectiveness in enhancing the relevance and recognition of micro-credentials. The system ensures that issued credentials are aligned with industry demands, improving graduates' employability and competitiveness. The findings indicate that a well-developed QMS for micro-credentials can address gaps in standardization and ensure that credentials are valid, reliable, and recognized across different sectors. The implementation of the QMS facilitates tailored skill acquisition, lifelong learning, and global recognition, making it a critical tool for enhancing workforce readiness and competitiveness.